Assessment Of Nursing And Nursing Technician Performance And Its Relationship To Patient Satisfaction (The Review of Diabetic Studies, 2024)
This research paper comprehensively examines the critical relationship between the performance of nursing personnel—encompassing both registered nurses and nursing technicians—and patient satisfaction, a cornerstone metric of healthcare quality. Recognizing the multifaceted nature of both constructs, the paper first establishes a conceptual foundation, defining nursing performance as an integration of technical competence and relational care, and patient satisfaction as a multidimensional subjective evaluation shaped by met expectations. It then critically reviews prevalent methodologies for performance assessment, arguing for triangulated systems that move beyond traditional checklists to incorporate multi-source feedback and patient-reported data. A synthesis of empirical evidence robustly confirms that specific performance dimensions, particularly interpersonal communication, responsiveness, and demonstrated clinical competence, are direct predictors of patient perceptions. Crucially, the analysis identifies the nursing work environment and staffing adequacy as pivotal mediating factors that either enable or constrain this relationship, with burnout and poor teamwork serving as significant barriers. The paper concludes that sustainable improvement requires an integrated practice model where comprehensive, formative performance assessment is systematically linked to targeted quality improvement initiatives and strategic investments in creating supportive practice environments. This approach is posited as essential for strengthening the nurse-patient interaction, optimizing care quality, and achieving enhanced patient satisfaction.